Influence of Different Surface Treatments and Type of luting Cement on the Retention of Glass Fiber Posts (Journal of Medical Sciences, 2022)
Background and objectives. The restoration of endodontically treated anterior teeth with excessive coronal destruction often requires a post and core system. One of the common treatments of these teeth is by using the glass-fiber posts. Although it offers better retention and stress distribution when used, debonding is still the most common mode of failure for glass fiber posts. Objectives: This study aimed to evaluate the bond strength of different surface treatments of glass fiber post systems using different adhesive systems via push out test. Methods. Forty-two extracted human incisors teeth were selected. The coronal aspect of each tooth was sectioned at 2 mm above the level of cement-enamel junction, and the remaining root received root canal therapy. Post spaces were prepared in all specimens to a depth of 10 mm. The teeth were divided randomly into three main groups, each of 14 specimens according to the glass-fiber post surface treatments: group I: control group (untreated glass-fiber posts surfaces), group II: glass-fiber posts subjected to sandblasting surface treatment with50μm aluminum oxide particles, group III: glass-fiber posts subjected to treated with 10% hydrofluoric acid. Each group has been subdivided into two subgroups, each of 7 specimens according to type of cement used as following: subgroup a: posts cemented by rely X Unicem, subgroup b: posts cemented by multilink N cement. Roots were then cut into three sections coronal, middle, and apical.  Push-out test was performed in a universal testing machine at a crosshead speed of 1 mm/minute, until the post segment was dis- lodged from the root section. The data were collected and analyzed with three-factorial ANOVA followed by pair-wise Tukey’s post-hoc tests (p ≤ 0.05) were performed to detect significance between subgroups. Statistical analysis was performed using SPSS IBM V.22.